Perancangan Penjadwalan Produksi untuk Mengoptimalkan Target Waktu Produksi pada IKM FBS - Nunung Nurhasanah; Widya Nurcahayanti Tanjung; Annura Minar Gayatri; Dimas Ayu (JURNAL TEKNIK INDUSTRI, 2018)
SME FBS is an industry engaged in the field of apparel. This industry is an industry that has been established for a long time. However, there are still shortcomings in the achievement of targets. Based on the above, optimization is needed in achieving the production time target. Optimization of production time is done by trial and error simulation. This research starts from the determination of standard time, identifies overtime machine time, optimizes initial production schedule scheduling with n Task m Processor and Lang's Algorithm, then design production scheduling with trial and error simulation on CMT A and CMT B. Results from this research to optimize the available work time for 4 days, CMT A based on historical data need to subcontract as many as 3 people, with cost of Rp.432.000. While based on forecast results need to subcontract as many as 5 people, with cost of Rp.628.000. CMT B based on history data need to do subcontract as much 6 people with cost equal to Rp.624.000, while based on forecast result need to do subcontract as much 22 people with cost equal to Rp.3.876.000. Standard production capacity for CMT A is 168 pieces with parallel work, if series can produce 216 pieces. For CMT B that is 720 pieces within 4 days, if 6 days is 1080 pieces.